PIK3CA-Related Overgrowth Spectrum From Diagnosis to Targeted Therapy: A Case of CLOVES Syndrome Treated With Alpelisib - Pagliazzi, Angelica; Oranges, Teresa; Traficante, Giovanna; Trapani, Chiara; Facchini, Flavio; Martin, Alessandra; Semeraro, Alessandro; Perrone, Anna; Filippeschi, Cesare; Giglio, Sabrina (Frontiers in Pediatrics, 2021)
PIK3CA-related overgrowth spectrum (PROS) is an umbrella term referring to various clinical entities, which share the same pathogenetic mechanism. These conditions are caused by somatic gain-of-function mutations in PIK3CA, which encodes the 110-kD catalytic α subunit of PI3K (p110α). These PIK3CA mutations occur as post-zygotic events and lead to a gain of function of PI3K, with consequent constitutional activation of the downstream cascades (e.g., AKT/mTOR pathway), involved in cellular proliferation, survival and growth, as well as in vascular development in the embryonic stage. PIK3CA-related cancers and PROS share almost the same PIK3CA mutational profile, with about 80% of mutations occurring at three hotspots, E542, E545, and H1047. These hotspot mutations show the most potent effect on enzymatic activation of PI3K and consequent downstream biological responses. If present at the germinal level, these gain-of-function mutations would be lethal to the embryo, therefore we only see them in the mosaic state. The common clinical denominator of PROS disorders is that they are sporadic conditions, presenting with congenital or early childhood onset overgrowth with a typical mosaic distribution. However, the severity of PROS is highly variable, ranging from localized and apparently isolate overgrowth to progressive and extensive lipomatous overgrowth associated with life-threatening vascular malformations, as seen in CLOVES syndrome. Traditional therapeutic approaches, such as sclerotherapy and surgical debulking, are often not curative in PROS patients, leading to a recrudescence of the overgrowth in the treated area. Specific attention has been recently paid to molecules that are used and studied in the oncogenic setting and that are targeted on specific alterations of the pathway PI3K/AKT/mTOR. In June 2018, Venot et al. showed the effect of Alpelisib (BYL719), a specific inhibitor for the p110α subunit of PI3K, in patients with PROS disorders who had severe or life-threatening complications and were not sensitive to any other treatment. In these cases, dramatic anatomical and functional improvements occurred in all patients across many types of affected organ. Molecular testing in PROS patients is a crucial step in providing the conclusive diagnosis and then the opportunity for tailored therapy. The somatic nature of this group of diseases makes challenging to reach a molecular diagnosis, requiring deep sequencing methods that have to be performed on DNA extracted from affected tissue. Moreover, even analyzing the DNA extracted from affected tissue there is no guarantee to succeed in detection of the casual somatic mutation, since the affected tissue itself is highly heterogeneous and biopsy approaches can be burdened by incorrect sampling or inadequate tissue sample. We present an 8-year-old girl with CLOVES syndrome, born with a large cystic lymphangioma involving the left hemithorax and flank, multiple lipomas, and hypertrophy of the left foot and leg. She developed severe scoliosis. Many therapeutic approaches have been attempted, including Sildenafil treatment, scleroembolization, laser therapy, and multiple debulking surgeries, but none of these were of benefit to our patient's clinical status. She then started treatment with Rapamycin from May 2019, without significant improvement in both vascular malformation and leg hypertrophy. A high-coverage Whole Exome Sequencing analysis performed on DNA extracted from a skin sample showed a mosaic gain-of-function variant in the PIK3CA gene (p.H1047R, 11% of variant allele frequency). Once molecular confirmation of our clinical suspicion was obtained, after a multidisciplinary evaluation, we decided to discontinue Sirolimus and start targeted therapy with Alpelisib (50 mg/day). We noticed a decrease in fibroadipose overgrowth at the dorsal level, an improvement in in posture and excellent tolerability. The treatment is still ongoing.